Mother's autonomy and child welfare: A new measure and some new evidence - Tanika Chakraborty; Prabal K. De (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
We construct a new, direct measure of female autonomy in household decision-making by creating an index from the principal components of a variety of household variables on which mother of a child takes decision. We then examine its impacts on her child's secondary education in Mexico and find that the children of Mexican mothers with greater autonomy in domestic decision making have higher enrolment in and lower probability of dropping out of secondary school. We use the relative proximity of spousal parents as instruments for relative autonomy to ameliorate the potential endogeneity between autonomy and welfare outcomes. We argue that omitted variables that may drive education and autonomy are likely to be uncorrelated with the ones driving location choice of families given the migration patterns in Mexico. However, the positive autonomy effect is weaker and non-existent for older children and for girls suggesting that gender-directed conditional cash transfer policies may not necessarily hasten educational and gender transition in the process of development.
Keywords: D1; I2; J1; 330; female empowerment; principal component; education; instrumental variable